GENITAL ULCERS CAUSED BY CYTOMEGALOVIRUS - Marcos-Pinto, Ana (2015)
The cytomegalovirus infection is prevalent in developed countries. The natural history of disease includes three phases: primoinfection (majority is asymptomatic), latency and reactivation. In certain immunosuppressive states, as in the case of transplantation and HIV infection, the virus can reactivate, occurring cutaneous manifestations, of what stands out the occurrence of genital ulcers. In these, co-infection with other etiologic agents is common, particularly with the herpes simplex virus, leading to more severe manifestations and difficulty in the differential diagnosis. In this context, it is relevant to know the pathogenesis of this virus and the diagnostics means available in order to optimize its therapy.